Taxonomy of the genus Doryllium Cobb, 1920 (Nematoda: Dorylaimida) with description of two new and a known species - Ahmad, Wasim; Ahad, Sumaya; Islam, Md. Niraul; Sturhan, Dieter (Zootaxa, 2018)
Two new and a known species of the genus Doryllium Cobb, 1920 are described and illustrated. Doryllium enigmatum n. sp. is characterized by a body length of 0.40–0.52 mm; continuous lip region; rounded lips; asymmetrical odontostyle, 5–6 µm long, and flanged odontophore 9–11 µm in length; pharynx with slender anterior part which expands into a slightly constricted pyriform basal bulb, occupying about 16–18% of total neck length; mono-opisthodelphic female genital system; 7–9 μm long anterior uterine sac; transverse vulva and rounded-hemispheroid tail. Doryllium asymmetricum n. sp. is characterized by its 0.52–0.63 mm long body; cap-like, slightly offset lip region; asymmetrical odontostyle, 6 µm in length and 9–11 µm long odontophore with weak flanges; pharynx with slender anterior part which expands gradually into pear-shaped basal bulb, occupying about 16.4–18.5% of total neck length; mono-opisthodelphic female genital system; anterior uterine sac 17–30 μm in length, filled with sperms; transverse vulva and rounded-hemispheroid tail. D. minor is redescribed based on specimens collected from several localities in India and Germany. The diagnosis of the genus Doryllium is emended and a valid list of species with their synonymies and a diagnostic compendium of all the known species is provided.